“A manager in the minds of doctors:” a comparison of new modes of control in European hospitals - Kuhlmann, E.; Burau, V.; Correia, T.; Lewandowski, R.; Lionis, C.; Noordegraaf, M.; Repullo, J. (BMC Health Services Research, 2013)
Background Hospital governance increasingly combines management and professional self-governance. This article maps the new emergent modes of control in a comparative perspective and aims to better understand the relationship between medicine and management as hybrid and context-dependent. Theoretically, we critically review approaches into the managerialism-professionalism relationship; methodologically, we expand cross-country comparison towards the meso-level of organisations; and empirically, the focus is on processes and actors in a range of European hospitals. Methods The research is explorative and was carried out as part of the FP7 COST action IS0903 Medicine and Management, Working Group 2. Comprising seven European countries, the focus is on doctors and public hospitals. We use a comparative case study design that primarily draws on expert information and document analysis as well as other secondary sources. Results The findings reveal that managerial control is not simply an external force but increasingly integrated in medical professionalism. These processes of change are relevant in all countries but shaped by organisational settings, and therefore create different patterns of control: (1) ‘integrated’ control with high levels of coordination and coherent patterns for cost and quality controls; (2) ‘partly integrated’ control with diversity of coordination on hospital and department level and between cost and quality controls; and (3) ‘fragmented’ control with limited coordination and gaps between quality control more strongly dominated by medicine, and cost control by management. Conclusions Our comparison highlights how organisations matter and brings the crucial relevance of ‘coordination’ of medicine and management across the levels (hospital/department) and the substance (cost/quality-safety) of control into perspective. Consequently, coordination may serve as a taxonomy of emergent modes of control, thus bringing new directions for cost-efficient and quality-effective hospital governance into perspective.